STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL PESERTA DIDIK DI SD NEGERI 141/VIII TUGU REJO, DESA BEDARO RAMPAK - Khodijah Rodiah; Eliva Sukma Cipta; Fitriyani Kosasih (STKIP Subang, 2026)
This study aimed to describe the strategies employed by Islamic Religious Education (PAI) teachers in developing students' emotional intelligence at SD Negeri 141/VIII Tugu Rejo, Bedaro Rampak Village. The research employed a qualitative approach using a descriptive research design. The research participants consisted of the principal, Islamic Religious Education teacher, classroom teachers, and students selected through purposive sampling. Data were collected through observations, interviews, and documentation and were analyzed using the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that Islamic Religious Education teachers implemented various strategies to foster students' emotional intelligence, including exemplary behavior, habituation of religious activities, educational communication, motivation, positive reinforcement, and character education integrated into the learning process. The effectiveness of these strategies was supported by collaboration among school principals, teachers, and parents in creating a conducive learning environment. However, several challenges were identified, including differences in students' characteristics, peer environmental influences, uncontrolled use of digital media, and limited parental assistance. The study concludes that the strategies implemented by Islamic Religious Education teachers play a significant role in enhancing students' ability to recognize, manage, and express emotions positively, thereby supporting the development of Islamic character and harmonious social relationships. These findings are consistent with contemporary studies emphasizing emotional intelligence as a fundamental component of Islamic education and character development.